PREVENTION AND TREATMENT OF DOMESTIC VIOLENCE IN LEGAL PERSPECTIVE - Samuel Saut Martua Samosir; Gautama Budi Arundhati; Firman Floranta Adonara (UPT Penerbitan Universitas Jember, 2022)
This community service is entitled